Gut Microbiota in Systemic Lupus Erythematosus and Correlation With Diet and Clinical Manifestations - Wang, Xiao; Shu, Qiang; Song, Lijun; Liu, Qi; Qu, Xiaoxia; Li, Ming (Frontiers in Medicine, 2022)
Despite the existing studies relating systemic lupus erythematosus (SLE) to changes in gut microbiota, the latter is affected by external factors such as diet and living environment. Herein, we compared the diversity and composition of gut microbiota in SLE patients and in their healthy family members who share the same household, to link gut microbiota, diet and SLE clinical manifestations. The study cohort included 19 patients with SLE and 19 of their healthy family members. Daily nutrition was assessed using a food frequency questionnaire (FFQ). Microbiota was analyzed using amplicons from the V4 regions of the 16S rRNA gene, to obtain microbiota diversity, taxa relative abundances and network analysis. The gut microbiota in the SLE group had lower alpha diversity and higher heterogeneity than the control group. SLE patients had decreased Acidobacteria, Gemmatimonadetes, Nitrospirae and Planctomycetes at the phylum level, and increased Streptococcus, Veillonella, Clostridium_XI, and Rothia at the genus level. Streptococcus was extremely enriched among patients with lupus nephritis. Lactobacillus, Clostridium_XlVa, Lachnospiracea_incertae_sedis and Parasutterella OTUs were associated with diet and clinical features of SLE. Finally, the gut microbiota of SLE patients remained different from that in healthy controls even after accounting for living conditions and diet.